Online Teaching Performance and the Aftermath of COVID-19: Results and Reflection from the Pilot Study - Yuhertiana, Indrawati; Rahmawati, Aulia; Sucahyati, Diarany; Izaak, Wilma Cordelia (HM Publisher, 2022)
The pandemic of COVID-19 that has been running for more than two years has changed the face of higher education. Various obstacles and challenges in teaching forced the entire academic community to adapt to the biggest health crisis. The research is a pilot study or introduction that aims to see how lecturers interpret their teaching performance during the pandemic and how they reflect on their teaching as an evaluation material. The method used here is a focus group discussion with eight lecturers from UPN Veteran Jawa Timur, Jakarta, and Yogyakarta, using thematic analysis to process the data. Three major thematics were found, namely, mental wellbeing, knowledge transfer, and creative pedagogies. It is recommended to conduct research with a larger scale of participants to be able to compare the performance of lecturers at UPN. The pandemic condition makes mental health a priority not only for the students but also the lecturers. Therefore, the combination of teaching creativity and the enhancement of technology are expected to reduce stress and burnout for both parties. It is recommended to further and scale up the number of research participants to have a more comprehensive understanding of how the pandemic impacted the learning process in higher education institutions.